Komodifikasi Dangdut Empat Generasi di Televisi: (Analisis Perluasan Pasar Media) - RUBIYANTO (LONTAR: Jurnal Ilmu Komunikasi, 2020)
The aim of this study is to provide readers insight into the practice of capitalism in the television industry, as their efforts seek profits through the expansion of the media market. Especially the practice of capitalism, which is represented by television content creators, in commodifying dangdut through program that are aired. To facilitate analysis, the author divides the study into four generations, namely monopoly, oligopoly, monopolistic compet ition, and perfect competition, which is related to the audience market and the advertiser's market. The approach used is qualitative with a critical paradigm, and historiography method. Data from interviews result of informants involved in the dangdut industry on television, participation observation, personal source documentation and the internet, the authors of the analysis to answer the purpose of this study. The result was found that in diffrent ways in each generation, dangdut as a culture of society was made commodity by television capitalists. The way through various genres of programs that are aired, they are looking for profits to expand the audience market and advertisers. Not only that, they also use television to spread their influence in society, to maintain their dominant position in the social order.